A Watermarking Application For Authentication Of Holy Quran - Tuncer, T.; Ertam, F.; Avci, E. (Ieee, 2013)
Nowadays, with the development of technology transfer to the information transmitted safely started to carry more importance to reach the desired aim. The science of information security is composed of steganography, watermarking, cryptography and authentication. Steganography is one of the subset of information security. In steganography objective data on the desired data to hide any cover. Thus, a computer file that appears cover data and data can be transmitted to the recipient in a hidden way. Digital watermarks may be used to verify the authenticity or integrity of the carrier signal or to show the identity of its owners. In this study, the fragile watermarking techniques will use pages of the Quran by using steganography methods. Our aim is to authenticate the raffle and to prevent the unauthorized distribution of printed or modified in establishing the digital samples. XOR, LSB and Border watermarking techniques will be used. The success rates of these techniques, PSNR will be analyzed according to the ratio.
Taibah-University International Conference on Advances in Information Technology for the Holy Quran and Its Sciences (NOORIC) -- DEC 22-25, 2013 -- Al Madinah, SAUDI ARABIA
Keywords: Watermarking; authentication; steganography; data hiding